Mathematics Teachers’ Awareness of the Characteristics of Professional Learning Communities and its Relationship with the Contemplative Practices and Teacher’s Self-Efficacy Mohammed Marji Alenezi / Mathematics Supervisor (Journal Of Educational and Psychological Researches, 2024)
The present research aims to identify the level of awareness of primary school mathematicsteachers in the city of Arar of the characteristics of professional learning communities, the degree of contemplative practices, and the degree of self-efficacy of their teachingIt also aims to identify the relationship between the level of awareness of mathematics teachers in the primary stage and the characteristics of professional learning communities and each of the "degrees of contemplative practices" and "degrees of self-efficacy of teaching." The researchers used the descriptive survey method. The study sample consisted of 163 mathematics teachers who teach at the primary level in public and private schools for boys in the city of Arar. The researchers used the questionnaire as a tool for data collection. The results revealed the level of awareness of mathematics teachers for the primary stage, and the characteristics of professional learning communities in the city of Arar displayed a general (high) indicator. The degree of contemplative practices of mathematics teachers for the primary stage in the city of Arar showed a general (high) indicator. The degree of teaching self-efficacy among mathematics teachers for the primary stage in the city of Arar manifested a general (high) indicator. There is a direct (positive) correlation between "the level of awareness of mathematics teachers for the primary stage of the characteristics of professional learning communities in the city of Arar" and "the degree of contemplative practices." There is a direct (positive) correlation between "the level of awareness of mathematics teachers for the primary stage of the characteristics of professional learning communities in the city of Arar" and "the degree of self-efficacy of teaching."